Wady wrodzoneUse of endovascular stents in multistage treatment in children with hypoplastic left heart syndrome – one centre experience - Moszura, Tomasz; Mazurek-Kula, Anna; Dryżek, Paweł; Moll, Jadwiga; Moll, Jacek; Sysa, Andrzej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Background: Interventional treatment is often a part of multistage palliative procedure for hypoplastic left heart syndrome (HLHS) which allows for reduction of number of surgical procedures in this special group of patients. Aim: The aim of this study was to estimate the efficiency of interventions with stent implantation during multistage treatment for HLHS. Material and methods: Between 1999 and 2007 we performed 23 interventions with stent implantation in 20 children with HLHS. There were 3 groups of interventions: group I – balloonplasty with stent implantation to narrowed pulmonary arteries (16 pts); group II – balloonplasty and stent implantation into aortic arch; group III – other interventions with stent implantation in HLHS pts. Results: In group I with stenosis and hypoplasia of pulmonary arteries stent implantation was successful in all 16 patients. In patients with aortic arch stenosis stent implantation led to aortic diameter increase from 4.5 mm to 8 mm and gradient reduction from 30 mmHg to 4 mmHg. Non-standard interventions (stent implantation into PDA, stent implantation into RV-PA shunt (right venticle-pulmonary artery shunt) and stent implantation into restrictive ASD (left pulmonary artery)) in critically ill patients resulted in improvement in patients’ condition. Conclusions: 1. Interventional procedures are efficient and safe methods in HLHS treatment. 2. Balloonplasty with stent implantation in pulmonary artery stenosis after Norwood procedure leads to increase of vessel diameter and pressure reduction, which improves the haemodynamics in pulmonary circulation. 3. Redilatation of implanted stent offers a possibility for vessel diameter increase during the child’s development. 4. Balloonplasty with stent implantation for recoarctation is an efficient method in HLHS patients’ treatment. 5. Non-standard interventions with stent implantation are an efficient method in palliative multistage treatment in HLHS.